Reclaiming the Old Testament for Christian preaching - Kent, Grenville J. R.; Block, Daniel Isaac (IVP Academic, 2010)
Preaching narrative : plot 13 / Laurence A. Turner -- Preaching narrative : characters / Paul J. Kissling -- Preaching from the law / Christopher J.H. Wright -- Preaching lament / Federico G. Villanueva -- Preaching praise poetry / David G. Firth -- Preaching wisdom / Tremper Longman III -- Preaching the Song of Solomon / Grenville J.R. Kent -- Preaching from Isaiah / H.G.M. Williamson -- Preaching Ezekiel / Daniel I. Block -- Preaching apocalyptic / Ernest C. Lucas -- Preaching the minor prophets / Alison Lo -- Preaching from difficult texts / Gordon J. Wenham -- Preaching Christ from the Old Testament / R.W.L. Moberly